The New Alexandrian Library (Oz, 1998)
It can be expected that the new Bibliotheca Alexandrina will bear a legacy that will reach as far into the future as its predecessor has provided to the past. We can potentially create an institution whose influence may span from the time of Alexander the Great, some two thousand years ago, to the present and beyond an additional two millennium.